THU0195 IFNα and its response proteins IP-10 and SIGLEC-1 as biomarkers of disease activity in systemic lupus erythematosus. (23rd January 2014) - Rose, T.; Gruetzkau, A.; Dähnrich, C.; Dzionek, A.; Hirseland, H.; Riemekasten, G.; Schlumberger, W.; Enghard, P.; Radbruch, A.; Burmester, G.-R.; Hiepe, F.; Biesen, R.
Abstract : Background: Over the decades, IFNα has been identified as a key cytokine predisposing and driving systemic lupus erythematosus pathology and is thus a frequently studied target molecule. It is assumed that IFNα can serve both as a biomarker of disease activity and as a companion diagnostic test for IFN inhibitors. IP-10 and Siglec-1, both response proteins of IFNα, have previously been shown to be suitable biomarkers for disease activity in SLE. A sensitive and reliable detection method for IFNα is indispensable, however a standard has yet to be established. Objectives: Evaluation and comparison of clinical efficacy of three biomarkers for interferon activity (measured directly and indirectly) and six traditional biomarkers to indicate current and prospective disease activity in SLE. Methods: IFNα (DELFIA), IP-10 (ELISA) and Siglec-1 expression on monocytes was measured by flow cytometry in 79 accurately characterized lupus patients and compared to serum titres of Anti-dsDNA (ELISA and RIA), Anti-dsDNA-NcX ELISA, Anti-Nuc ELISA, C3 and C4. 31 clinically quiescent patients were monitored for flares over the course of 180 days. Disease activity was evaluated using BILAG-2004. Results: Increased IFN biomarkers were found for IFNα in 53%, IP-10 in 47% and Siglec-1 in 79% of this lupus cohort. IFNα (r=0.45; p<0.0001) and Siglec-1 (r=0.54; p<0.0001) correlated better with BILAG-2004 than IP-10 (r=0.38; p=0.0002), Farr assay (r=0.40; p=0.0001), Anti-dsDNA-NcX ELISA (r=0.28; p=0.0061), Anti-dsDNA ELISA (r=0.31; p=0.0025), Anti-Nuc ELISA (r=0.25; p=0.0121), C3 (r=-0.43; p<0.0001) and C4 (r=-0.33; p=0.0013). The best predictors of SLE flares were low lymphocyte count, short disease duration, mild clinical activity, low complement C3 and high IFNα. Conclusions: IFNα and Siglec-1 expression on monocytes emerged as the best biomarkers of disease activity in lupus patients. Therefore, implementation of IFN biomarkers in standard lupus diagnostics should be reappraised, especially in view of new and emerging anti-IFN-directed therapies. References: Bengtsson AA, Sturfelt G, Truedsson L, et al. Activation of type I interferon system in systemic lupus erythematosus correlates with disease activity but not with antiretroviral antibodies. Lupus 2000;9:664–71. Kong KO, Tan AW, Thong BYH, et al. Enhanced expression of interferon-inducible protein-10 correlates with disease activity and clinical manifestations in systemic lupus erythematosus. Clin Exp Immunol 2009;156:134–40. Biesen R, Demir C, Barkhudarova F, et al. Sialic acid-binding Ig-like lectin 1 expression in inflammatory and resident monocytes is a potential biomarker for monitoring disease activity and success of therapy in systemic lupus erythematosus. Arthritis Rheum 2008;58:1136–45. Rönnblom L, Alm GV, Eloranta M-L. The type I interferon system in the development of lupus. Semin Immunol 2011;23:113–21. Yao Y, Higgs BW, Richman L, et al. Use of type I interferon-inducible mRNAs as pharmacodynamic markers and potential diagnostic markers in trials with sifalimumab, an anti-IFNalpha antibody, in systemic lupus erythematosus. Arthritis Res Ther 2010;12 Suppl 1:S6. Disclosure of Interest: None Declared